Pattern of childhood tuberculosis among the patients admitted in Dhaka Shishu (Children) Hospital - Sultana, Akhand Tanzih; Gathia, Ribika; Huda, Md Mahmudul; Begum, Jostna Ara; Kamruzzaman, -; Amin, Md Ruhul (Northern International Medical College Journal, 2017)
Background : Tuberculosis (TB) poses a serious threat to public health throughout the world but disproportionately afflicts low-income nations. Every year 8.7 million people are affected by TB in the world and six to 10 per cent of them are children. Objective : The aim of this study was to determine the pattern of childhood tuberculosis (TB) among the patients admitted in Dhaka Shishu (Children) Hospital. Methods : All inpatient diagnosed TB cases (age 0-15 years) who registered in DOTS clinic of Dhaka Shishu Hospital for treatment of tuberculosis during January, 2015 to December, 2015 were included in this prospective study. Total 91 patients of either sex were enrolled. After taking informed consent data were collected on demographic profile, clinical profile and mortality rate. Data were analyzed in SPSS version 16. Results : The most common form of TB was EPTB (67.03%) followed by PTB (32.97%). The common age group was 1- 5 years in both extra pulmonary tuberculosis (EPTB) and pulmonary tuberculosis (PTB). Male predominance was seen in (EPTB) cases. EPTB was predominantly meningeal (27.8%). Case fatality rate was 14.29%. Mortalities were more common beetween1-5 years of age and among them 4 were females (30.77%) and 9 were males (69.23%).Tubercular meningitis (TBM) was the main cause of death which comprised 6.59%. Conclusion : In this study Tuberculosis was common in younger age. EPTB was common in the children, which was predominantly tubercular meningitis. The majority of mortalities occurred due to tubercular meningitis. Northern International Medical College Journal Vol.8(2) January 2017: 213-215